Representation Of Gender Pictured Out In “English In Mind Student’s Book 3” - Salsabila, Tasya; Perpisa, Lili; Sesmiyanti, Sesmiyanti (JUPE : Jurnal Pendidikan Mandala, 2023)
This research is motivated to understand how gender roles are portrayed in textbooks, especially in the context of English language teaching in accordance with the Merdeka Curriculum. This study aims to determine the gender representation in the English textbook titled "English In Mind Student's Book 3" for grade X in high school, published by Cambridge University. This research employs a quantitative method. As the data source for this research, the researcher focuses on 5 text stories within the short story texts. The findings reveal that there are differences in the use of words and pronouns to depict males and females. The gender representation in the textbook does not align with the principles of equity upheld by the Merdeka Curriculum in Indonesia. The Merdeka Curriculum promotes equal rights and responsibilities between males and females. However, this teaching book has not achieved a balanced gender role portrayal,contradicting those values. The Merdeka Curriculum emphasizes the importance of fostering character and skills in students with a gender equality perspective, as reflected in the fifth tenet of Pancasila that guarantees equal rights for all.